The epidemic of Dengue virus type-2 Cosmopolitan genotype on Reunion Island relates to its active circulation in the Southwestern Indian Ocean neighboring islands. Issue 4 (April 2019) - Pascalis, Hervé; Turpin, Jonathan; Roche, Marjolaine; Krejbich, Pascale; Gadea, Gilles; Nten, Célestine Atyame; Desprès, Philippe; Mavingui, Patrick
Abstract: Reunion Island is currently experiencing an epidemic caused by Dengue virus type-2 (DENV-2) resulting in over 6, 763 cases from austral summer 2017 to winter 2018. Phylogenetic analyses on two non-imported cases of dengue infection from Reunion Island highlight a regional circulation of DENV-2 Cosmopolitan lineage 1 virus on both Reunion Island and the Seychelles.